Optimization and thermal stability of TiAlN-Mo multilayers - Tavares, C. J. (2005)
In this work we focus on the optimization and thermal stability of nanocomposite TiAlN/Mo multilayers that were produced by reactive magnetron sputtering on high-speed steel substrates, with modulation periods below 5 nm. These multilayers were annealed between 600– 900 ºC for 1 h in a vacuum furnace. Preliminary X-ray diffraction results reveal that these coatings are very stable up to 900 ºC, since the multilayer chemical modulation is not severely affected. At intermediate annealing temperatures the modulation period decreases due to interdiffusion at the interface, resulting in a thicker interface between metal/nitride and hence decreasing the thickness of those layers.